2020
DOI: 10.1002/adma.202000513
|View full text |Cite
|
Sign up to set email alerts
|

High Spin Hall Conductivity in Large‐Area Type‐II Dirac Semimetal PtTe2

Abstract: Spin-orbit torque (SOT) provides an ultrafast and energy-efficient means to switch magnetization, which is of fundamental and technical importance for spintronic devices. [1][2][3][4][5] A typical SOT device consists of heavy metal/ferromagnet (HM/FM) bilayer, where the HM (e.g., Pt, W, Ta, etc.) converts charge current into spin current mainly due to the spin Hall effect (SHE) and then exerts a torque on the adjacent FM enabling magnetization manipulation. To improve the energy efficiency of SOT-driven magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
106
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 57 publications
15
106
2
1
Order By: Relevance
“… 17 19 The quantitative estimation of the SHC and auto-oscillations current density in our TaS 2 /Py hold valuable information for several spintronic applications. Evidently, the interface of our TaS 2 /Py bilayer, as confirmed by cross-sectional TEM and supported by parameters extracted from X-ray reflectivity measurements, is clean in contrast to other works using exfoliated sheets and nonuniform growth where extrinsic contributions from strain and defect-related issues 17 , 48 , 38 reduce the charge-spin conversion efficiency. First-principles calculations based on the density functional theory (DFT) reveal the role of SOC for lifting the degeneracy in the band structure of TaS 2 /Py.…”
Section: Discussionsupporting
confidence: 74%
“… 17 19 The quantitative estimation of the SHC and auto-oscillations current density in our TaS 2 /Py hold valuable information for several spintronic applications. Evidently, the interface of our TaS 2 /Py bilayer, as confirmed by cross-sectional TEM and supported by parameters extracted from X-ray reflectivity measurements, is clean in contrast to other works using exfoliated sheets and nonuniform growth where extrinsic contributions from strain and defect-related issues 17 , 48 , 38 reduce the charge-spin conversion efficiency. First-principles calculations based on the density functional theory (DFT) reveal the role of SOC for lifting the degeneracy in the band structure of TaS 2 /Py.…”
Section: Discussionsupporting
confidence: 74%
“…191,192 Hence, modifying the metalsemiconductor contact interface is an effective strategy to improve device performance. Specifically, using metallic 2D materials (graphene, 193 some 1 T phase TMDs 47,187,[194][195][196][197] ) as electrodes for (opto)electronics through epitaxy growth 35 or phase transition 198,199 will alleviate the pining effect. In addition, transferring the prefabricated metal electrodes can also avoid creating defects and strains, resulting in an atomically sharp and near perfect metal/2D semiconductor interface.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the TMDs in this way allows us to pinpoint important differences and similarities in the observed torques. (Xu et al, 2020) PtTe 2 (3-20 nm) CVD Py (2.5, 5.0, 7.5, 10 nm)…”
Section: Discussion On Recent Progressmentioning
confidence: 99%
“…More recently, PtTe 2 /Py devices (Xu et al, 2020) have shown a high spin-torque conductivity for the in-plane DL torque σ y e 1.6 × 10 5 (Z/2e)(Ωm) − 1 . This value is one order of magnitude (or larger) than the values encountered in other TMD-based devices and comparable to devices based on heavy-metal or topological-insulators.…”
Section: Semi-metallic Tmdsmentioning
confidence: 99%